Peryferie stanu wojennego? — casus województwa sieradzkiego - Czyżewski, Andrzej (Dzieje Najnowsze, 2016)
Peripheries of Martial Law? — the Case of the Voiovdeship of Sieradz The presented text intends to describe breakthrough events and processes in the socio–political history of post–war Poland from the viewpoint of terrains located along the peripheries of the chief current of events of the period. The author wondered to what extent could the paradigm of universal resistance against the communist authorities be applied in regions situated outside the prime centres of contestation. In doing so, he transferred his reflections to the reality of the marital law period and the range of the former voivodeship of Sieradz. The point of departure for the ensuing deliberations is a depiction of the specificity of a totally agricultural area, only slightly urbanised, and with no structure of the pre–August opposition. Next, the author considered the period of the ”Solidarity Revolution” in those terrains, and, finally, concentrated his attention on analysing phenomena that can be regarded as a symptom of social resistance against the governance of the Military Council of National Salvation (WRON). The text ends with an attempt at a balance sheet of the described phenomena, conducted with the help of the social sciences, i.e. the conception of “group contestation”.